Formulasi Blue Ocean Strategy : Studi Kasus Kopi Gayo di Kabupaten Takengon - Samrin Samrin; Irawan Irawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to identify and analyze the blue ocean strategy formulation for gayo coffee products. One of the most discussed topics today in the business world is how to escape the intense Red Ocean and how to create an indisputable Blue Ocean. Strategies for achieving distinct competitive advantages through innovative information technology (i.e., problem identification and implementation), which enable creating an undeniable market space, business based on efficiency and effectiveness. A remarkable fact about Gayo's Blue Ocean Strategy coffee products is that its rapid growth has not come from attracting competing customers from the existing Red Ocean market, but from creating the Blue Ocean market (3PL market), which the existing incumbents have noticed. , and also from building a new business model based on the ubiquitous-oriented 3PL system. Analyzed through the Four Actions Framework and characterized as Blue Ocean, this case study provides valuable information on how a business strengthened its competitive advantage from the Red Ocean as it transitioned to the Blue Ocean by leveraging the creation of unrivaled market space, creating and capturing new demand